2011
DOI: 10.1039/c1cc13860j
|View full text |Cite
|
Sign up to set email alerts
|

Highly diastereo- and enantioselective NHC-catalyzed [3+2] annulation of enals and isatins

Abstract: The chiral N-heterocyclic carbene bearing a proximal hydroxy group derived from L-pyroglutamic acid was found to be an efficient catalyst for the [3+2] annulation of enals and isatins to give the corresponding spirocyclic oxindolo-γ-butyrolactones in good yield with good diastereo- and enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
63
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(66 citation statements)
references
References 57 publications
1
63
0
Order By: Relevance
“…and 94 % ee) when B3, having a bulky N-2-isopropylphenyl group, was utilized (entry 5). As reported, [8] the bulky substituent of B3 could circumvent the possible C1 addition of the generated Breslow intermediate, and thus facilitate the C3 addition. Solvent screening revealed that reaction went smoothly in various solvents with a slightly better diastereoselectivity observed in diethyl ether or 1,4-dioxane (entries 6- With the optimized reaction conditions in hand, the scope with respect to the o-quinone methides and enals was examined (Scheme 2).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…and 94 % ee) when B3, having a bulky N-2-isopropylphenyl group, was utilized (entry 5). As reported, [8] the bulky substituent of B3 could circumvent the possible C1 addition of the generated Breslow intermediate, and thus facilitate the C3 addition. Solvent screening revealed that reaction went smoothly in various solvents with a slightly better diastereoselectivity observed in diethyl ether or 1,4-dioxane (entries 6- With the optimized reaction conditions in hand, the scope with respect to the o-quinone methides and enals was examined (Scheme 2).…”
mentioning
confidence: 88%
“…[7] In 2004, Bode et al and Glorius et al independently reported the pioneering NHC-catalyzed [3+2] annulation of enals with aldehydes to give g-butyrolactones (Scheme 1 a). [8] Then, g-lactams were synthesized by reaction with imines.…”
mentioning
confidence: 99%
“…Employing chiral azolium catalysts B-E resulted in a wide range of diastereo-and enantioselectivities, with the 2,6-diethylphenyl substituted triazolium precatalyst B being the catalyst of choice (entry 12-15). We discovered that with only 5 mol % catalyst B similar levels of conversion and selectivity were obtained (entry 16).With the optimized reaction conditions, we surveyed isatins with varying nitrogen protecting groups and substitution around the aromatic ring (Table 2, [3][4][5][6][7][8][9][10][11][12][13][14]. Electron withdrawing and donating substituents on the aromatic ring were well accommodated, providing the lactone products in 1.6-3.0:1 dr and 77-99% ee.…”
mentioning
confidence: 99%
“…With the optimized reaction conditions, we surveyed isatins with varying nitrogen protecting groups and substitution around the aromatic ring ( Table 2, [3][4][5][6][7][8][9][10][11][12][13][14]. Electron withdrawing and donating substituents on the aromatic ring were well accommodated, providing the lactone products in 1.6-3.0:1 dr and 77-99% ee.…”
mentioning
confidence: 99%
See 1 more Smart Citation